Question
upstudy study bank question image url

2. \( 5 x^{2}-21 x-54=0 \)

Ask by Barker Ortiz. in South Africa
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are \( x = 6 \) and \( x = -\frac{9}{5} \).

Solution

We need to solve the quadratic equation   5x² – 21x – 54 = 0. There are several methods to solve a quadratic equation. Here, we'll show both the factoring method and the quadratic formula. ───────────────────────────── Step 1. Factoring We look for two numbers a and b such that when the quadratic is factored in the form   (ax + m)(bx + n) = 0, we get   a·b = 5 (the coefficient of x²) and m·n = –54 (the constant term), and the cross terms satisfy   a·n + b·m = –21 (the coefficient of x). Since 5 is a prime number, a likely factorization is to assign 5 to one of the binomials. Try writing the expression as   (x – 6)(5x + 9) = 0. Let’s check by expanding:   (x – 6)(5x + 9) = 5x² + 9x – 30x – 54 = 5x² – 21x – 54. Since it matches the given quadratic, the factorization is correct. Setting each factor equal to zero gives: 1) x – 6 = 0  ⟹ x = 6, 2) 5x + 9 = 0  ⟹ 5x = –9  ⟹ x = –9/5. ───────────────────────────── Step 2. Quadratic Formula Alternatively, we can use the quadratic formula, which for an equation ax² + bx + c = 0 is:   x = [–b ± √(b² – 4ac)] / (2a). Here, a = 5, b = –21, and c = –54. Plugging these in: 1. Calculate the discriminant:   Δ = b² – 4ac      = (–21)² – 4·5·(–54)      = 441 + 1080      = 1521. 2. Find the square root of Δ:   √1521 = 39       (since 39² = 1521). 3. Substitute into the formula:   x = [–(–21) ± 39] / (2·5)   x = [21 ± 39] / 10. Thus, we get two solutions:   x = (21 + 39) / 10 = 60 / 10 = 6,   x = (21 – 39) / 10 = (–18) / 10 = –9/5. ───────────────────────────── Final Answer The solutions to the equation 5x² – 21x – 54 = 0 are   x = 6  and  x = –9/5.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To solve the quadratic equation \( 5x^{2}-21x-54=0 \), you can use the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \). Plugging in \( a = 5 \), \( b = -21 \), and \( c = -54 \), you get: 1. Calculate the discriminant: \( b^2 - 4ac = (-21)^2 - 4(5)(-54) = 441 + 1080 = 1521 \). 2. Hence, \( x = \frac{21 \pm \sqrt{1521}}{10} \), which simplifies to \( x = \frac{21 \pm 39}{10} \). This results in two potential solutions: \( x = 6 \) and \( x = -1.8 \). Now you’ve got the x-values where the equation equals zero! Keep in mind that solving quadratics can sometimes yield irrational or complex numbers, which can feel daunting. Common mistakes include miscalculating the discriminant or forgetting to simplify your final answer. When in doubt, double-check each arithmetic step to ensure you're on the right track!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy